Digital Content Provision and Optimal Copyright Protection - Guo, Liang; Meng, Xiangyi (Management Science, 2015)
Advances in digital technologies have led to an increasing concern about piracy for providers of digital content (e.g., e-books, games, music, software, videos). Yet controversies exist over the influence of copyright protection on firm profitability. The objective of this paper is to provide an alternative rationale for the growing anti-protection trend and to investigate optimal copyright enforcement and quality provision in a monopoly setting. The proposed economic mechanism centers on the influence of copyright protection on consumer search when consumers can get to know the firm’s actions (e.g., price, quality) only after costly search. We show that more stringent copyright protection can induce the consumers to rationally expect lower ex post surplus, thus exerting a negative strategic effect on the consumers' willingness to search. This strategic effect may outweigh the positive main effect on the relative attractiveness of the authorized versus the pirated product, which can hence explain the optimality of incomplete and even zero copyright protection policies in markets where consumer prepurchase search is important (e.g., information goods, digital products). It is also because of this strategic effect that the firm may provide lower quality as copyright enforcement increases. Interestingly, quality unobservability can moderate this strategic effect and thus lead to an increasing incentive for copyright protection. This paper was accepted by Pradeep Chintagunta, marketing.